The Antiproliferative and Apoptosis-Inducing Effects of the Red Macroalgae Gelidium latifolium Extract against Melanoma Cells - Eka Sunarwidhi Prasedya (MDPI AG, 2021)
The red macroalga Gelidium latifolium is widely distributed in the coastal areas of Indonesia. However, current knowledge on its potential biological activities is still limited. In this study, we investigated the potential bioactive compounds in Gelidium latifolium ethanol extract (GLE), and its cytotoxic effects against the murine B16-F10 melanoma cell line. GLE shows high total phenolic content (107.06 ± 17.42 mg GAE/g) and total flavonoid content (151.77 ± 3.45 mg QE/g), which potentially contribute to its potential antioxidant activity (DPPH = 650.42 ± 2.01 µg/mL; ABTS = 557.01 ± 1.94 µg/mL). ESI-HR-TOF-MS analysis revealed large absorption in the [M-H]- of 327.2339 m/z, corresponding to the monoisotopic molecular mass of brassicolene. The presence of this compound potentially contributes to GLE’s cytotoxic activity (IC50 = 84.29 ± 1.93 µg/mL). Furthermore, GLE significantly increased the number of apoptotic cells (66.83 ± 3.06%) compared to controls (18.83 ± 3.76%). Apoptosis was also confirmed by changes in the expression levels of apoptosis-related genes (i.e., p53, Bax, Bak, and Bcl2). Downregulated expression of Bcl2 indicates an intrinsic apoptotic pathway. Current results suggest that components of Gelidium latifolium should be further investigated as possible sources of novel antitumor drugs.